Energy-related CO2 emissions from the manufacturing and transportation of cement. (19th November 2010) - Teo, Evelyn Ai Lin; Lin, Guangming; Lim, Lewis Jui Wee
Climate change is widely accepted as a global challenge. As a key building material, cement industry contributes significantly to the global anthropogenic carbon dioxide emissions. This study examines the energy-related CO2 emitted from cement production and transportation. A case study provided the basis for this study. The finding indicates that the energy intensity for cement from 'cradle to Singapore sea port' is approximately 4.25 MJ/kg of cement. The conversion factor recommended by the Inter-Governmental Panel on Climate Change (IPCC) was utilised to convert the energy intensity into carbon intensity. The energy-related CO2 intensity from 'cradle to Singapore sea port' is estimated to be 0.4 kg CO2/kg-1 of cement. By knowing the exact percentage of each fuel consumed, it is more accurate to attribute carbon dioxide emission to each process, which would significantly improve the reliability of estimated outcomes of CO2 intensity for cement manufacturing and transportation.